Birokrasi, Perilaku dan Budaya Organisasi dalam Lembaga Pendidikan Islam Roudlotul Athfal UIN Sunan Kalijaga Yogyakarta - Djunawir Syafar (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
This research discusses bureaucracy and organizational behaviour and culture in Islamic education institute i.e., Roudlotul Athfal UIN Sunan Kalijaga Yogyakarta. This research aims to study the implementation of institutional bureaucracy and to build organisational behaviour and culture. This is a qualitative research applying three methods of data collection, namely: (1) observation, (2) in-depth interview, (3) emphasizing the value of dialogue ​​(small colloquium, discussion or sharing), (2) Integrating Islamic values ​​to build organizational behaviour such as honesty, discipline and mutual respect. (3) Cultural acculturation as part of the organizational cultural identity, such as maintaining the grassroots culture including how to behave, how to communicate in certain language and other social interactions. These aspects ​​turn into the basic values of institutional bureaucracy in facing various challenges, social changes as well as competition among numerous Islamic educational institutions.